2020
DOI: 10.1007/s12671-020-01492-6
|View full text |Cite
|
Sign up to set email alerts
|

Common Factors Underlying the Five Facets of Mindfulness and Proposed Mechanisms: a Psychometric Study Among Meditators and Non-meditators

Abstract: Objectives This study investigated whether common factors underlie the established mindfulness facets, as assessed by the Five Facet Mindfulness Questionnaire (FFMQ) and some of the mechanisms, which have been previously proposed to explain the beneficial effects of mindfulness on mental health. Methods Multigroup exploratory structural equation models (ESEM) were fitted to samples of non-meditators and meditators (total N = 3265) to (1) identify the number of factors that underlie the facets and mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 54 publications
(99 reference statements)
3
15
1
2
Order By: Relevance
“…However, body awareness was associated with less depression and anxiety but only in the meditator sample. Nevertheless, our results are in line with the findings of Bednar et al (2020). They found that the factor which included body awareness and observing was significantly positively related to depression among meditators, and significantly positively associated with anxiety among nonmeditators.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, body awareness was associated with less depression and anxiety but only in the meditator sample. Nevertheless, our results are in line with the findings of Bednar et al (2020). They found that the factor which included body awareness and observing was significantly positively related to depression among meditators, and significantly positively associated with anxiety among nonmeditators.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, future research should focus more on the role of the frequency of meditation practice. Another unexpected result of our study was that high levels of observing were related to higher levels of body awareness, which in turn were (Bednar et al, 2020;Rudkin et al, 2018).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The strong ability to persevere and postpone need gratification makes that they are les tuned to signals of their body and tend to choose their actions on basis on what they think that they should do and not on what they feel. Relaxation exercises, meditation and mindfulness exercises can be helpful to become more receptive to signals of the body again (Bednar et al, 2020).…”
Section: Phase 2: Recovery Of the Stress Systemmentioning
confidence: 99%
“…Za takim właśnie rozwiązaniem zdają się przemawiać wyniki innych badań, które dowodzą, że pozycje testowe narzędzi mierzących uważność powinny być kon ceptualizowane raczej jako wielowymiarowe niż specyficzne (czynnik ogólny uważność oraz specyficzne konstrukty poznawcze; por. Aquado i in., 2015;Bednar, Voracek, Tran, 2020).…”
Section: Trafność Wewnętrznaunclassified